LUMINESCENCE OF CERIUM DOPED YTTRIUM ALUMINUM GARNET CERAMICS SYNTHESIZED IN THE FIELD OF RADIATION FLUX - Alpyssova, G.K.; Lisitsyn, V.M.; Karipbayev, Zh.T.; Golkovski, M.G. (KU Publ., 2021)
The paper presents the results of ceramic samples’ dependence of luminescent properties on their position in the crucible during irradiation. For the synthesis, a blend of powders of aluminum oxide, yttrium oxide and cerium oxide was prepared. The ratio of oxides in the charge corresponded to stoichiometric. The particles of the oxide powders had a size of about 1 micron and less. Synthesis was carried out on gas pedal electron accelerator at Institute of Nuclear Physics SB RAS (Novosibirsk). Luminescent properties were measured on spectrofluorimeter SM 2203 "SOLAR" under excitation by monochromatic radiation at 450 nm. Two types of samples differing in the value of bulk density and the prehistory of yttrium oxide were investigated.
Keywords: white LEDs; yttrium-aluminum garnet; phosphor; ceramics; synthesis in the radiation field